Electrochemical properties of enclosed silicon nanopowder electrode inserted in integrated TiO2 nanotubes grown on titanium for Li-ion battery. (10th October 2016) - Ha, Jong-Keun; Chauhan, Ghanshyam S.; Ahn, Jou-Hyeon; Ahn, Hyo-Jun; Cho, Kwon-Koo
Graphical abstract: Highlights: A facile and novel method was used for Si-powder anode in lithium-ion battery. Si insertion and binder coating were applied by using the brushing method. The TiO2 nanotube was used as the support storing the Si nanopowder. Coating the binder on surface was played a role for restraining the Si secession. This study is to improve the cycling performance for Si-powder anode. Abstract: Si-based electrodes are being designed for use in Lithium-ion batteries with an aim at attaining large energy density and long and stable cycle life. In view of its high theoretical capacity (4200 mAh g −1 ), Si has huge potential as anode material. In this study, we report improvement in the cycling performance of the cell designed with electrode having Si-nanopowder contained in the TiO2 nanotube array, which is not a composite material. Si-nanopowder is incorporated on the nanotube arrays by three different protocols. The Si-nanopowder electrode prepared by using the facile brushing method, proposed in this study, followed by the surface coating with binder exhibited high cycling behavior. Especially, the cell made with the anode material fabricated by brushing of Si-nanopowder into the TiO2 nanotube array, having diameter of 150 nm, yield high capacity retention of 1824.9 mAh g −1 up to 300 cycles in the lithiation process at 0.1 C-rate.